Carbon-based structure material surface loosening in-situ rapid self-repairing SiC-HfSi2-HfB2 coating and preparation method thereof

Through the atomic bridging method of Si-Hf-B and the volume ratio adjustment of HfSi2 to HfB2, the problem of oxidation of the HfB2-SiC coating in ultra-high temperature environments is solved, and the in-situ rapid self-repair is achieved, which significantly improves the dynamic stability and oxygen barrier ability of the coating.

CN119569468APending Publication Date: 2025-03-07HENAN ACAD OF SCI CARBON MATRIX COMPOSITES RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411758801.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing HfB2-SiC coating oxidizes under ultra-high temperature environment to produce low melting point B2O3, resulting in pore formation, destroying the oxygen-resisting structure, and the oxidation and vaporization of the boride causes the pinning point of the Hf oxide to become porous and loose, affecting the dynamic stability of the coating.

Method used

The atomic bridging method of Si-Hf-B is adopted, and the volume ratio adjustment of HfSi2 and HfB2 is adjusted to shorten the repair path of Si elements for Hf oxidation and loosening, realizing in-situ repair, improving repair efficiency and enhancing dynamic oxygen barrier capabilities.

Benefits of technology

Significantly reduce the oxidative weight gain curve fitting data, improve the dynamic stability and long-term protection ability of the coating, and enhance the barrier effect on oxygen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569468A_ABST
    Figure CN119569468A_ABST
Patent Text Reader

Abstract

The invention relates to the field of aerospace structure new materials, in particular to a carbon-based structure material surface loosening in-situ rapid self-repairing SiC-HfSi2-HfB2 coating and a preparation method thereof, and the atom bridging mode of the coating is Si-Hf-B. The manufacturing method comprises the following steps: preparing and uniformly mixing Hf, B and Si simple substances, preparing HfSi2-HfB2 composite powder by using a self-propagating combustion method, mixing SiC powder, and carrying out coating densification treatment and surface polishing on the surface of a carbon matrix by using a low-temperature hot pressing technology. The coating provided by the invention adopts a Si-Hf-B bridging mode. Compared with the defect that in the prior art, due to separated distribution of boride and silicide components, the timeliness of the repairing process is poor, the repairing path of the Si element on Hf oxidation loosening can be effectively shortened, the in-situ repairing effect on Hf oxidation loosening is achieved, the repairing aging is fast, and the repairing effect is remarkable. A control experiment verifies that the fitting data of the oxidation weight gain curve is obviously reduced, and the method has the effects of improving the repair efficiency and enhancing the dynamic oxygen barrier capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new aerospace structural materials, and in particular to a carbon-based structural material surface loosening in-situ rapid self-repairing SiC-HfSi2-HfB2 coating and a preparation method thereof. Background Art

[0002] Carbon-based structural materials are widely used in cutting-edge fields such as aerospace and strategic missiles. However, due to the oxidation sensitivity of carbon, carbon-based structural materials are very susceptible to oxidation in high-temperature oxygen environments above 400°C, which greatly limits their development. In extensive research, ultra-high temperature ceramic (UHTC) coatings have been considered as one of the reliable methods to extend the working life of carbon-based structural materials in high-temperature environments.

[0003] In recent years, hafnium diboride (HfB2) has become an ideal material for preparing ultra-high temperature ceramic coatings due to its high melting point, low thermal expansion, low oxygen diffusion coefficient at high temperature and high chemical stability. Among them, HfB2-SiC coating has attracted the attention of many scholars due to its excellent high temperature performance. Under high temperature environment, Hf oxide is embedded in the SiO2 glass layer, which improves the thermal stability of SiO2 and limits the ability of microcrack propagation, thereby reducing the erosion of oxygen on the carbon matrix. However, under ultra-high temperature environment above 1700℃, the low melting point B2O3 produced by HfB2 oxidation will volatilize violently, resulting in the formation of a large number of pores in the coating, thereby destroying the oxygen barrier structure of the coating. Therefore, it is necessary to further optimize its design to improve the dynamic stability of the coating at ultra-high temperature.

[0004] In order to optimize the dynamic stability of HfB2-SiC-based coatings at ultra-high temperatures, Zhang Menglin et al. (Zhang Menglin. Preparation and high oxygen barrier mechanism of transition metal silicide modified hafnium boride coating [D]. China University of Mining and Technology, 2022) used transition metal silicide as the second phase silicon source, which improved the sealing effect of the glass film to a certain extent and extended the high-temperature protection life of the coating. However, the problem of porous and loose Hf oxide pinning points caused by boride oxidation and gasification has not been improved, and the loose holes will further provide a path for oxygen to penetrate, thereby aggravating the deterioration of the dynamic stability of the coating's oxygen barrier structure, which is not conducive to the long-term stable protection of the coating at ultra-high temperatures. Based on this, there is an urgent need for a self-healing coating that can provide stable protection at ultra-high temperatures and a preparation method thereof. Summary of the invention

[0005] The technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a SiC-HfSi2-HfB2 coating for in-situ rapid self-repair of the surface porosity of a carbon-based structural material and a preparation method thereof are provided, through the atomic bridging of Si-Hf-B, the repair path of the Si element for the oxidative porosity of Hf is shortened, the in-situ repair effect for the oxidative porosity of Hf is achieved, the repair efficiency is effectively improved, and the dynamic oxygen barrier capability is enhanced.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is as follows:

[0007] A carbon-based structural material surface loosening in-situ rapid self-repairing SiC-HfSi2-HfB2 coating, wherein the atomic bridging mode of the coating is Si-Hf-B.

[0008] As an improvement, the volume ratio of HfSi2 to HfB2 in the coating ranges from 40:60 to 10:90.

[0009] The present invention also discloses a method for preparing a carbon-based structural material surface loosening in-situ rapid self-repairing SiC-HfSi2-HfB2 coating, comprising the following steps:

[0010] S1. Proportionally configure and uniformly mix Hf, B, and Si elements;

[0011] S2. The mixed Hf, B, Si single substance was prepared by self-propagating method HfSi2-HfB2 composite powder, the obtained HfSi2-HfB2 composite powder was ground and mixed with SiC powder to obtain SiC-HfSi2-HfB2 composite powder;

[0012] S3. Using the SiC-HfSi2-HfB2 composite powder obtained in S2 as the powder source, a coating densification treatment is performed on the surface of the carbon substrate using low temperature hot pressing technology;

[0013] S4. After the treatment is completed, the product is polished to obtain a loosened in-situ self-repairing SiC-HfSi2-HfB2 coating.

[0014] As an improvement, the molar ratio of Hf, B and Si in step S1 is in the range of 100:142:58 to 100:187:13.

[0015] As an improvement, in the HfSi2-HfB2 composite powder described in step S2, the ratio of HfSi2 to HfB2 ranges from 40:60 to 10:90.

[0016] As an improvement, in the SiC-HfSi2-HfB2 composite powder described in step S3, the volume ratio of SiC, HfSi2 and HfB2 ranges from 40:24:36 to 40:6:54.

[0017] As an improvement, the specific method of the low temperature hot pressing technology in step S3 is: sintering in an SPS sintering furnace, the sintering temperature is 1500°C, the heating rate is 5°C / min, the pressure is 25MPa, and the holding time is 5min.

[0018] The advantages of the present invention are:

[0019] The coating of the present invention adopts a Si-Hf-B bridging method. Compared with the defect of poor timeliness of the repair process caused by the separation distribution of boride and silicide components in the prior art, the present invention can effectively shorten the repair path of Si element for Hf oxidation loosening, achieve an in-situ repair effect for Hf oxidation loosening, and the repair time is fast and the effect is significant. The control experiment verified that the oxidation weight gain curve fitting data of the present invention is significantly reduced, which has the effect of improving the repair efficiency and enhancing the dynamic oxygen barrier capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a surface microscopic morphology of the SiC-HfSi2-HfB2 coating obtained in Example 1 of the present invention.

[0021] Figure 2 This is a surface microscopic morphology of the SiC-HfSi2-HfB2 coating obtained in Example 2 of the present invention.

[0022] Figure 3 This is a surface microscopic morphology of the SiC-HfSi2-HfB2 coating obtained in Example 3 of the present invention.

[0023] Figure 4 This is a microscopic morphology of the surface of the SiC-HfSi2-HfB2 coating obtained in Example 4 of the present invention.

[0024] Figure 5 This is a microscopic morphology of the surface of the SiC-HfSi2-HfB2 coating obtained in Comparative Example 1 of the present invention.

[0025] Figure 6 Fitting of the weight gain curves of SiC-HfSi2-HfB2 coatings obtained in Examples 1 to 4 of the present invention and Comparative Example 1 at 1700°C high temperature oxidation. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0027] Embodiment 1:

[0028] This embodiment discloses a SiC-HfSi2-HfB2 coating for in-situ rapid self-repair of the surface porosification of a carbon-based structural material.

[0029] In the coating, the volume ratio of HfSi2 to HfB2 is 40:60, and the atomic bridging mode in the coating is Si-Hf-B.

[0030] The preparation method of this embodiment comprises the following steps:

[0031] S1. Prepare and evenly mix Hf, B, and Si elements in a molar ratio of 100:142:58.

[0032] S2. The mixed Hf, B, Si single substance was prepared by self-propagating method HfSi2-HfB2 composite powder, the obtained HfSi2-HfB2 composite powder HfSi2 and HfB2 product ratio of 40:60;

[0033] The obtained HfSi2-HfB2 composite powder is then ground and mixed with SiC powder to obtain SiC-HfSi2-HfB2 composite powder; during grinding and mixing, the volume ratio of SiC powder to HfSi2-HfB2 composite powder is 40:60, and the volume ratio of SiC, HfSi2 and HfB2 in the obtained SiC-HfSi2-HfB2 composite powder is 40:24:36.

[0034] S3. Using the SiC-HfSi2-HfB2 composite powder obtained in S2 as the powder source, a coating densification treatment is performed on the surface of the carbon substrate using low temperature hot pressing technology;

[0035] The specific method of low temperature hot pressing technology is: sintering in an SPS sintering furnace, the sintering temperature is 1500°C, the heating rate is 5°C / min, the pressure is 25MPa, and the insulation time is 5min.

[0036] S4. After the treatment is completed, the product is polished to obtain a loosened in-situ self-repairing SiC-HfSi2-HfB2 coating.

[0037] The surface micromorphology of the in-situ rapid self-repairing SiC-HfSi2-HfB2 coating obtained in this embodiment is shown in Figure 1 As shown, the 1700℃ high temperature oxidation weight gain curve is fitted as follows Figure 6 shown.

[0038] Example 2

[0039] This embodiment discloses a SiC-HfSi2-HfB2 coating for in-situ rapid self-repair of the surface of a carbon-based structural material.

[0040] In the coating, the volume ratio of HfSi2 to HfB2 is 30:70, and the atomic bridging mode in the coating is Si-Hf-B.

[0041] The preparation method of this embodiment comprises the following steps:

[0042] S1. Prepare and evenly mix Hf, B, and Si elements in a molar ratio of 100:158:42.

[0043] S2. The mixed Hf, B, Si single substance was prepared by self-propagating method HfSi2-HfB2 composite powder, the obtained HfSi2-HfB2 composite powder HfSi2 and HfB2 product ratio of 30:70;

[0044] The obtained HfSi2-HfB2 composite powder is then ground and mixed with SiC powder to obtain SiC-HfSi2-HfB2 composite powder; during grinding and mixing, the volume ratio of SiC powder to HfSi2-HfB2 composite powder is 40:60, and the volume ratio of SiC, HfSi2 and HfB2 in the obtained SiC-HfSi2-HfB2 composite powder is 40:18:42.

[0045] S3. Using the SiC-HfSi2-HfB2 composite powder obtained in S2 as the powder source, low-temperature hot pressing technology is used to perform coating densification treatment on the surface of the carbon substrate.

[0046] The specific method of low temperature hot pressing technology is: sintering in an SPS sintering furnace, the sintering temperature is 1500°C, the heating rate is 5°C / min, the pressure is 25MPa, and the insulation time is 5min.

[0047] S4. After the treatment is completed, the product is polished to obtain a loosened in-situ self-repairing SiC-HfSi2-HfB2 coating.

[0048] The surface micromorphology of the in-situ rapid self-repairing SiC-HfSi2-HfB2 coating obtained in this embodiment is shown in Figure 2 As shown, the 1700℃ high temperature oxidation weight gain curve is fitted as follows Figure 6 shown.

[0049] Embodiment 3:

[0050] This embodiment discloses a SiC-HfSi2-HfB2 coating for in-situ rapid self-repair of the surface of a carbon-based structural material.

[0051] In the coating, the volume ratio of HfSi2 to HfB2 is 20:80, and the atomic bridging mode in the coating is Si-Hf-B.

[0052] The preparation method of this embodiment comprises the following steps:

[0053] S1. Prepare and evenly mix Hf, B, and Si elements in a molar ratio of 100:174:26.

[0054] S2. The mixed Hf, B, Si single substance was prepared by self-propagating method HfSi2-HfB2 composite powder, the obtained HfSi2-HfB2 composite powder HfSi2 and HfB2 product ratio of 20:80;

[0055] The obtained HfSi2-HfB2 composite powder is then ground and mixed with SiC powder to obtain SiC-HfSi2-HfB2 composite powder; during grinding and mixing, the volume ratio of SiC powder to HfSi2-HfB2 composite powder is 40:60, and the volume ratio of SiC, HfSi2 and HfB2 in the obtained SiC-HfSi2-HfB2 composite powder is 40:12:48.

[0056] S3. Using the SiC-HfSi2-HfB2 composite powder obtained in S2 as the powder source, low-temperature hot pressing technology is used to perform coating densification treatment on the surface of the carbon substrate.

[0057] The specific method of low temperature hot pressing technology is: sintering in an SPS sintering furnace, the sintering temperature is 1500°C, the heating rate is 5°C / min, the pressure is 25MPa, and the insulation time is 5min.

[0058] S4. After the treatment is completed, the product is polished to obtain a loosened in-situ self-repairing SiC-HfSi2-HfB2 coating.

[0059] The surface micromorphology of the in-situ rapid self-repairing SiC-HfSi2-HfB2 coating obtained in this embodiment is shown in Figure 3 As shown, the 1700℃ high temperature oxidation weight gain curve is fitted as follows Figure 6 shown.

[0060] Embodiment 4:

[0061] This embodiment discloses a SiC-HfSi2-HfB2 coating for in-situ rapid self-repair of the surface porosification of a carbon-based structural material.

[0062] In the coating, the volume ratio of HfSi2 to HfB2 is 10:90, and the atomic bridging mode in the coating is Si-Hf-B.

[0063] The preparation method of this embodiment comprises the following steps:

[0064] S1. Prepare and evenly mix Hf, B, and Si elements in a molar ratio of 100:187:13.

[0065] S2. The mixed Hf, B, and Si elements are used to prepare HfSi2-HfB2 composite powder by self-propagating method, and the HfSi2-HfB2 composite powder has a product ratio of HfSi2 to HfB2 of 10:90;

[0066] The obtained HfSi2-HfB2 composite powder is then ground and mixed with SiC powder to obtain SiC-HfSi2-HfB2 composite powder; during grinding and mixing, the volume ratio of SiC powder to HfSi2-HfB2 composite powder is 40:60, and the volume ratio of SiC, HfSi2 and HfB2 in the obtained SiC-HfSi2-HfB2 composite powder is 40:6:54.

[0067] S3. Using the SiC-HfSi2-HfB2 composite powder obtained in S2 as the powder source, low-temperature hot pressing technology is used to perform coating densification treatment on the surface of the carbon substrate.

[0068] S4. After the treatment is completed, the product is polished to obtain a loosened in-situ self-repairing SiC-HfSi2-HfB2 coating.

[0069] The surface micromorphology of the in-situ rapid self-repairing SiC-HfSi2-HfB2 coating obtained in this embodiment is shown in Figure 4 As shown, the 1700℃ high temperature oxidation weight gain curve is fitted as follows Figure 6 shown.

[0070] Comparative Example 1:

[0071] The SiC-HfSi2-HfB2 coating on the surface of the carbon-based structural material involved in this embodiment is a conventional SiC-HfSi2-HfB2 coating without Si-Hf-B atomic bridges inside, and the ratio of HfSi2 to HfB2 is 0:100 (volume ratio).

[0072] The preparation method of this reference example comprises the following steps:

[0073] (1) preparing and uniformly mixing Hf, B, and Si elements in a molar ratio of 100:200:0;

[0074] (2) preparing HfSi2-HfB2 composite powder with a volume ratio of 0:100 by a self-propagating method from the mixed Hf, B, and Si elements, and further grinding and mixing with SiC powder to obtain SiC-HfSi2-HfB2 composite powder;

[0075] (3) Using SiC-HfSi2-HfB2 composite powder with a volume ratio of 40:0:60 as the powder source, the coating densification treatment was carried out on the surface of the carbon substrate by low-temperature hot pressing technology;

[0076] (4) After the treatment, the product is polished to obtain a loosened in-situ self-repairing SiC-HfSi2-HfB2 coating.

[0077] The surface micromorphology of the in-situ rapid self-repairing SiC-HfSi2-HfB2 coating obtained in this comparative example is shown in Figure 5 As shown, the 1700℃ high temperature oxidation weight gain curve is fitted as follows Figure 6 shown.

[0078] It can be found that, unlike Examples 1 to 4, there is no Si-Hf-B atomic bridging inside the coating obtained in this comparative example, and all Si elements are connected to C. Although the surface micromorphology of the sample obtained in this comparative example is not significantly different from that of Examples 1 to 4, it is found that after high-temperature oxidation at 1700°C, its oxidation weight gain curve fitting data is significantly higher than that of the samples of Examples 1 to 4. In other words, since the coating obtained in Examples 1 to 4 utilizes the bridging of Si-Hf-B at the atomic level, it effectively shortens the repair path of Si elements for Hf oxidation loosening, achieves an in-situ repair effect for Hf oxidation loosening, and has a fast repair time and significant effect, which is manifested as a significant reduction in the oxidation weight gain curve fitting data of the samples of Examples 1 to 4, achieving the effect of improving the repair efficiency and enhancing the dynamic oxygen barrier capacity.

[0079] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A carbon-based structural material surface loosening in-situ rapid self-repair SiC-HfSi2-HfB2 coating, characterized in that: The atomic bridging mode of the coating is Si-Hf-B.

2. According to claim 1, a carbon-based structural material surface loosening in-situ rapid self-repairing SiC-HfSi2-HfB2 coating is characterized in that: The volume ratio of HfSi2 to HfB2 in the coating ranges from 40:60 to 10:

90.

3. A method for preparing a SiC-HfSi2-HfB2 coating for in-situ rapid self-repair of a surface loosening of a carbon-based structural material according to claim 1, characterized in that: The steps include: S1. Proportionally configure and evenly mix Hf, B, and Si elements; S2. The mixed Hf, B, Si single substance was prepared by self-propagating method HfSi2-HfB2 composite powder, the obtained HfSi2-HfB2 composite powder was ground and mixed with SiC powder to obtain SiC-HfSi2-HfB2 composite powder; S3. Using the SiC-HfSi2-HfB2 composite powder obtained in S2 as the powder source, a coating densification treatment is performed on the surface of the carbon substrate using low temperature hot pressing technology; S4. After the treatment is completed, the product is polished to obtain a loosened in-situ self-repairing SiC-HfSi2-HfB2 coating.

4. The method for preparing a carbon-based structural material surface loosening in-situ rapid self-repairing SiC-HfSi2-HfB2 coating according to claim 3, characterized in that: The molar ratio of Hf, B and Si in step S1 ranges from 100:142:58 to 100:187:

13.

5. The method for preparing a carbon-based structural material surface loosening in-situ rapid self-repairing SiC-HfSi2-HfB2 coating according to claim 3, characterized in that: In the HfSi2-HfB2 composite powder described in step S2, the ratio of HfSi2 to HfB2 ranges from 40:60 to 10:

90.

6. The method for preparing a carbon-based structural material surface loosening in-situ rapid self-repairing SiC-HfSi2-HfB2 coating according to claim 3, characterized in that: In the SiC-HfSi2-HfB2 composite powder described in step S3, the volume ratio of SiC, HfSi2 and HfB2 ranges from 40:24:36 to 40:6:

54.

7. The method for preparing a carbon-based structural material surface loosening in-situ rapid self-repairing SiC-HfSi2-HfB2 coating according to claim 3, characterized in that: The specific method of the low temperature hot pressing technology in step S3 is: sintering in an SPS sintering furnace, the sintering temperature is 1500°C, the heating rate is 5°C / min, the pressure is 25MPa, and the insulation time is 5min.

Citation Information

Patent Citations

  • Carbon-based composite material surface glass ceramic anti-oxidation coating and preparation method thereof

    CN116730747A

  • METHOD FOR PREPARATION OF DENSE HfC(Si)-HfB2 COMPOSITE CERAMIC

    US20210179499A1